2017
DOI: 10.1002/anie.201611761
|View full text |Cite
|
Sign up to set email alerts
|

An Unconventional Mechanistic Insight into SCF3 Formation from Difluorocarbene: Preparation of 18F‐Labeled α‐SCF3 Carbonyl Compounds

Abstract: We discovered trifluoromethylthiolation occurred through sulfuration of difluorocarbene with elemental sulfur for the first time, which overrides our putative and long-standing trifluoromethyl anion-based theory. This mechanistic elucidation not only allows the discovery of an unprecedented chemical process for the formation of thiocarbonyl fluoride, but also enables transition metal-mediated trifluoromethylthiolation and [18F]trifluoromethylthiolation of α-bromo carbonyl compounds with broad substrate scope a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 64 publications
(31 reference statements)
0
34
0
1
Order By: Relevance
“…The method was compatible with aliphatic substrates bearing electron‐withdrawing or electron‐donating groups in RCCs of 22–83 %. Subsequently, the authors found α‐bromocarbonyl compounds could also be converted into α‐[ 18 F]SCF 3 carbonyl derivatives (Scheme 32 B) . An unconventional reaction mechanism was discovered through the identification of a key intermediate, a thiocarbonyl fluoride, in the formation of alkyl‐SCF 3 compounds.…”
Section: Labeling Methods With Fluorine‐18mentioning
confidence: 99%
“…The method was compatible with aliphatic substrates bearing electron‐withdrawing or electron‐donating groups in RCCs of 22–83 %. Subsequently, the authors found α‐bromocarbonyl compounds could also be converted into α‐[ 18 F]SCF 3 carbonyl derivatives (Scheme 32 B) . An unconventional reaction mechanism was discovered through the identification of a key intermediate, a thiocarbonyl fluoride, in the formation of alkyl‐SCF 3 compounds.…”
Section: Labeling Methods With Fluorine‐18mentioning
confidence: 99%
“…Die Methode war kompatibel mit aliphatischen Substraten, die elektronenziehende oder elektronenschiebende Gruppen enthalten, wobei RCC von 22–83 % erreicht werden konnten. Anschließend fanden die Autoren, dass auch α‐Bromcarbonyle in die α‐[ 18 F]SCF 3 ‐Carbonyle umgewandelt werden konnten (Schema 32 B) . Bei der Bildung von Alkyl‐SCF 3 ‐Verbindungen wurde anhand der Identifizierung des Schlüsselintermediats Thiocarbonylfluorid ein unkonventioneller Reaktionsmechanismus entdeckt.…”
Section: Markierungsmethoden Mit Fluor‐18unclassified
“…[25] Difluoromethylene phosphobetaine 2 (triphenylphosphoniodifluoroacetate, PDFA), in the presence of elemental sulfur,w as found to generate thiocarbonyl fluoride 3,t hat in turn, after interaction with CsF,p romotes the a-trifluoromethylthiolation of carbonyl compounds (Scheme 16). Trifluoromethylthiolation of a-halo ketones using [Ag(SCF 3 )I] À + K. Very recently,Xiao and Liang, reported useful mechanistic informationf or the formation of trifluoromethylthio anion from difluorocarbene, sulfur,a nd fluoride, and the subsequent interactions between the generated SCF 3 anion and transition metals.…”
Section: Reactions With Nucleophilic Trifluoromethylthiolating Reagentsmentioning
confidence: 99%
“…Very recently,Xiao and Liang, reported useful mechanistic informationf or the formation of trifluoromethylthio anion from difluorocarbene, sulfur,a nd fluoride, and the subsequent interactions between the generated SCF 3 anion and transition metals. [25] Difluoromethylene phosphobetaine 2 (triphenylphosphoniodifluoroacetate, PDFA), in the presence of elemental sulfur,w as found to generate thiocarbonyl fluoride 3,t hat in turn, after interaction with CsF,p romotes the a-trifluoromethylthiolation of carbonyl compounds (Scheme 16).…”
Section: Reactions With Nucleophilic Trifluoromethylthiolating Reagentsmentioning
confidence: 99%